The child-centred curriculum design: its characteristics and implications for educational practice (1999)
Curriculum has different definitions but certain basic agreements exist about some elements of the definitions of the term. Curriculum has been regarded in this paper as the totality of planned, organised and intended learning experiences provided by the school for the all round development of the pupil. However, the kind of curriculum given by the British colonialists was not child centered. Many curriculum designs have been offered by experts in curriculum studies and the subject designed is one of them. Learning within this design focuses on language activities - thinking, listening, reading and writing.The earlier curriculum experts emphasized on the subject centered curriculum design. Learners' needs and interests were not considered; various school subjects to which learners were exposed were not seriously considered. The emphasis on the subject centered curriculum design has been a very serious concern to present writers. This explains why the major purpose of this paper was the examination of the child-centred curriculum design. The implication of the design for eductional practice was also examined. It was therefore concluded that the child centered curriculum design could be very effective because it centres around learners interest and needs. For the purpose of effective implementation of the design, some fundamental questions were provided which teachers, instructors and curriculum planners should consider in the teaching-learning process.